2017
DOI: 10.4209/aaqr.2015.03.0196
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bacteria in Filtering Facepiece Respirators and Effects of Artificial Saliva/Perspiration on Bacterial Survival and Performance of Respirators

Abstract: This study seeks the optimal method for recovering loaded bacteria from filtering facepiece respirators (FFRs) and investigates the effects of artificial saliva (AS), artificial perspiration (AP) and storage conditions on the survival of bioaerosols and the filter performance of FFRs. Bioaerosols were generated using a Collison nebulizer in a test system and loaded on either N95 or surgical masks. Elution using centrifuge at 3500 rpm for ten min followed by vortexing for one min yielded a high relative surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…A facemask, as a kind of simple and convenient respirator, is widely used in daily life. It has been demonstrated that wearing facemasks for a long time can reduce the probability of infection from influenza-like illnesses (MacIntyre et al, 2009;Natarajan et al, 2016;Lin et al, 2017). Especially, functional facemasks are recommended for frontline healthcare workers to prevent splashes and sprays of blood, body fluids and the spread of infection from the wearer (Siegel et al, 2007;Agarwal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A facemask, as a kind of simple and convenient respirator, is widely used in daily life. It has been demonstrated that wearing facemasks for a long time can reduce the probability of infection from influenza-like illnesses (MacIntyre et al, 2009;Natarajan et al, 2016;Lin et al, 2017). Especially, functional facemasks are recommended for frontline healthcare workers to prevent splashes and sprays of blood, body fluids and the spread of infection from the wearer (Siegel et al, 2007;Agarwal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The main test variable in this study is the survival of bacteria that were loaded on N95 FFRs that were decontaminated by various methods under worst‐case temperature and humidity, which prevail when an FFR is placed in a zipper bag in a healthcare worker's pocket with the goal of preventing cross‐contamination, and touching of the respirator . In the experiment, B. subtilis spores were the tested microbial strain; a six‐jet Collison nebulizer (BGI, Waltham, MA) sprayed the spores into a test system, shown in Figure , where they were loaded on N95 FFRs by suction to simulate the respiratory flow of workers during intensive activity . The experimental FFR was an N95 FFR (8210, 3M, St. Paul, MN), certified by NIOSH.…”
Section: Methodsmentioning
confidence: 99%
“… Ethanol: Ethanol with various concentrations and volumes was added to the center of the surface of the N95 FFR using a pipette, the FFR was then dried in a petri dish that was placed in a biosafety cabinet (BSC) for 10 minutes. Bleach: A 0.4 mL volume of bleach with various concentrations (5.4% (w/w) as Cl 2 : original; 2.7%: one part bleach to one part of deionized water; 0.54%: one part bleach to nine parts of deionized water) was added to the center of the surface of the N95 FFR using a pipette, the FFR was then dried in a petri dish in a BSC for 10 minutes. UV: An N95 FFR was placed 10 cm below a 6 W handheld UV lamp (model UVGL‐58, VUP LLC, Upland, CA) that emitted a wavelength of 254 nm (UVC, 18.9 mW/cm 2 ) or 365 nm (UVA, 31.2 mW/cm 2 ). Both sides of each N95 FFR were exposed for different times ‐ 1, 2, 5, 10 and 20 minutes ‐ in a BSC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For future respirator design, facial fit is a critically important parameter to consider for desired protection efficiency. Another problem lies with common materials of masks, such as active carbon and polypropylene melt-brown fabric, which might serve as hotbeds for bacterial growth and virus breeding on the mask, eventually causing secondary pollutants to people and the environment (Lin et al, 2015). In an effort to minimize the problem, some studies focus on developing new materials for respiratory masks, e.g., adding antibacterial agents such as nano-silver to the material of masks (Borkow et al, 2010;Natarajan et al, 2016) or using carbon nanotubes as filtration material (Guan and Yao, 2010;Xu and Yao, 2011;Zou and Yao, 2015).…”
Section: Bioaerosol Concentration Monitoring In a Classroom Before Dmentioning
confidence: 99%